Small bowel feeding: do you pay the price for bypassing the stomach?. Issue 2 (March 2022) - Bond, Ashley; Czapran, Adam; Lal, Simon
Abstract : Purpose of review: Hydration and nutritional support is a vital part of medical care, thus a clear understanding of the optimal approach is vital for medical professionals. This is a particularly pertinent issue for patients admitted to a critical care setting. This article aims to define the advantages and disadvantages of gastric and postpyloric feeding in the critical care setting, thus aiding decision-making for clinicians. Recent findings: Within the article, the main themes covered are those relating to enteral feeding tube placement, the impact of enteral feeding route on ventilator-associated pneumonia, optimization of enteral tube feeding in critical care and the impact that a chosen route may have upon gastrointestinal function. Summary: The value of enteral feeding in critical illness is proven beyond doubt and the simplest approach has long been 'if the gut works, use it'. If gastric feeding is not able to be established or is not tolerated then jejunal feeding should be considered as a preferable alternative to parenteral nutrition. Improving access to service or techniques for postpyloric tube placement would assist in optimizing nutritional support in the critical care setting.